Financial Anxiety and the Adoption of Islamic Financial Services: A Behavioral Law and Psychology Perspective - Didik Kusno Aji Nurgoho (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
The regulation and development of Islamic financial services have largely been based on normative rational assumptions that position consumers as fully rational and autonomous decision-makers. This approach tends to overlook the psychological conditions under which economic decisions are made, particularly financial anxiety arising from economic uncertainty, financial pressure, and social risk. This study aims to examine how financial anxiety influences the adoption of Islamic financial services and to assess how this condition challenges the rationality assumption embedded in Islamic economic law. In addition, the study seeks to develop a conceptual framework of Islamic economic law informed by behavioral law and mental well-being, grounded in maqāṣid al-sharī‘ah. This research employs a qualitative normative–conceptual and analytical approach. The analysis draws on Islamic legal sources, including the Qur’an, Hadith, fiqh al-mu‘āmalāt, fatwas, and maqāṣid al-sharī‘ah literature, complemented by a systematic review of studies in economic psychology, behavioral finance, and Islamic economic psychology. Data are analyzed using qualitative content and thematic analysis. The findings indicate that financial anxiety significantly shapes individuals’ intentions and behaviors in adopting Islamic financial services, thereby challenging purely rational and normative regulatory assumptions. Integrating behavioral and mental well-being perspectives is essential for developing a more contextual, empathetic, and human-centered framework of Islamic economic law.